Peran Aktif Kegiatan Taruna-Taruni Akademi Maritim Nusantara Banjarmasin Dalam Meningkatkan Bakat dan Minat Untuk Kegiatan Masyarakat di Banjarmasin - Hadiansyah; Ahmad Hairi (Akademi Maritim Nusantara Banjarmasin, 2023)
Abstract Role is a dynamic aspect of position (status). If a person performs his rights and obligations according to his position, then he is carrying out a role. While obligations are everything that must be done by everyone in carrying out their lives. In the Indonesian dictionary it is also explained that role is an action performed by someone in an event. Being active can be announced in the behavior of a child through to adolescence where at that time of course they are looking for identity in recognizing their future life, and when they are active they already have talent from themselves so they will be more active and motivated individually, then on family support and surroundings. The PkM method uses a participatory approach, in which the author is actively involved in every mentoring process in the field. The result of this assistance is an increase in the enthusiasm of the cadets in participating in activities according to the goals requested and an increase in the interest and talents that the cadets have. Training activities for cadets at the Banjarmasin Archipelago Maritime Academy campus were continued in several places such as halls and fields for training activities. The results of the Community Service activities towards the active role of the activities of the Banjarmasin Archipelago Maritime Academy Cadets in increasing Talent and Interest for Community activities in Banjarmasin, is an effort which of course starts with discipline in recognizing the talents and interests favored by cadets as provisions in their work. what they have to display and of course benefit society, with the aim of entertainment, art or mental sharpening that is played when appearing in public, of course providing good for themselves and others, by honing the talents and interests that cadets have are able to grow generations which is useful for the family environment as motivation, and of course the success that is focused can be an additional business or activity in adding knowledge and the economy in the future. Keywords. role, active, talent interest.